Edukasi Dan Pelatihan Pemeriksaan Payudara Sendiri (Sadari) Pada Remaja Putri - Anis Khotimah; Woro Ispandiyah; Sulistiawati (STIKes Ibnu Sina Ajibarang, 2024)
One type of disease that is a major health and death problem throughout the world is cancer. The most feared cancer disease for women throughout the world, including Indonesia, is breast cancer. Of all the cancer cases, Indonesia ranks first, namely breast cancer with 65,858. In fact, if the examination is carried out at an early stage it can reduce a person's death rate. Therefore, it is important to train in breast self-examination (BSE) from a young age. The aim of this education is to increase the knowledge of young women about breast self-examination (BSE) to detect breast cancer. The target of this education is 61 MA Mafaza Bantul students from Classes X to XII. The design of this activity is to carry out one measurement up front (pre test) before the treatment and after that another measurement is carried out (post test). In this activity, the paired T-test is used to determine the influence or relationship between one variable and another variable. The results show that the Sig. (2-tailed) is 0.000 < 0.05, then H0 is rejected and Ha is accepted, there is an average difference between the pre-test and posttest, so there is an increase in knowledge, attitudes and behavior in young women at MA MAFAZA Bantul, which means there is an influence of training breast self-examination (BSE).